Dominasi Peradaban Barat Dalam Pendidikan Islam - Hasanuddin Hasanuddin (Universitas Islam Negeri Alauddin, 2014)
Deteriorations of education and culture of Islam after the 13th century was marked in weakness of thoughts until the 18th century. In addition, the destruction of Baghdad and Granada as the centre of education and Islam culture became the main factors of Islam degradation. In other side European accepted philosophy and science from Moslem. while Moslems themselves started to ignore philosophy and science. It had caused the resurrections of European gradually and it was the impact of deteriorations in education and Islamic culture. Therefore, if all Moslems are desire to renascent, they must start to learn and follow the western development in any aspects which is included of educational aspect.